Gender Development Index Sensitivity Analysis of Sustainable Coastal Rural Development - Riniwati, Harsuko; Utami, Tiwi Nurjanati; Wati, Lina Asmara; Islamiyah, Ira Tri; Sazmi, Rivera Dewi (Journal of Indonesian Tourism and Development Studies, 2023)
The Sustainable Development Goals (SDGs) are a global action plan agreed upon by world leaders, including Indonesia, to end poverty, reduce inequality, and protect the environment. Realize the SDGs are strongly influenced by economic, social, and environmental indicators. The balance between economic, social, and environmental is the goal of sustainable development. The success of development is determined by the quality of human beings, which consists of women and men. We can use the Gender Development Index (GDI) to measure the quality of human development based on gender. The gender gap will affect the quality of development. Provinces that have many coastal villages have a high gender gap. This study aims to analyze the sensitivity of the gender development index in realizing sustainable coastal rural development. Data obtained from coastal rural experts. Data analysis using multipolicy. The results show that the gender development index has a high sensitivity in realizing sustainable development in coastal villages. It is evident from the results of the analysis that the position of the gender development index ranks first in achieving the success of sustainable development in coastal villages. Suggestions for research: it is necessary to increase the gender development index strategy. The trick is to manage the indicators that make up the GDI, where the progress of each indicator for women cannot be lower than for men. At a minimum, the progress of women's resources is the same as that of men, so their GDI will increase. Keywords: Coastal Rural, Gender Development Index, Sustainable Development.